Medicinal Uses of Garlic - a mini review - Akter, Sharmin; Ahsan, Monira; Islam, Sheikh Nazrul (Bangladesh Journal of Nutrition, 2019)
Nature is serving as an abundant source of medicinal herbs and plants. Garlic is a medicinal herb with potential nutritional values. It has been used as a potential medicinal herb. Since time immemorial, garlic is a remedy for various physiological disorders. This review focuses on the medicinal uses of garlic in treatment and prevention of several chronic and acute diseases including infection of multidrug resistant Shigella infection. Bangladesh J. Nutr. Vol. 32, December 2019, P: 61-72